Speculative Security : The Politics of Pursuing Terrorist Monies - De Goede, Marieke (Book collections on Project MUSE., 2012)
Since the terrorist acts of September 11, 2001, finance and security have become joined in new ways to produce particular targets of state surveillance. In Speculative Security, Marieke de Goede describes how previously unscrutinized practices such as donations and remittances, especially across national borders, have been affected by security measures that include datamining, asset freezing, and transnational regulation. These "precrime" measures focus on transactions that are perfectly legal but are thought to hold a specific potential to support terrorism. The pursuit of suspec.